Rapid evaluation protocol for HydrogPeroxide and Ultraviolet Radiation resistance using Lesion Mimic Mutant rice (Oryza sativa L.) - Dong-Soo, Park; Soo-Kwon, Park.; Sang-Min, Kim.; Woon-Ha, Hwang; Hoe-Jeong, Wang.; Sang-Gu, Kang.; Hang-Won, Kang.; Gihwan, Yi. (2011)
Ultraviolet (UV) radiation can induce an increase in hydrogen peroxide (H2O2) production which could both inflict injury to crops affecting growth and productivity. Response of plants to UV and H2O2 may vary not only among species but also among cultivars. A protocol for screening UV and H2O2 resistance was developed using lesion mimic mutant (LMM) rice lines to detect resistant rice breeding lines related to abiotic stresses where H2O2 is involved. To date, there is no standard method or protocol yet that has been defined for the rapid and reliable detection of resistant rice lines using UV and H2O2, Screening under field and uncontrollable environmental effects such as temperature, humidity, rainfall, and solar radiation/duration. Thus, a rapid and reproducible laboratory protocol for H2O2 and UV radiation is necessary to reduce time and resources with desirable outputs. LMM rice lines were preferably used than the cultivars since LMM are known to be more sensitive to stress signals and spontaneously develop necrotic lesions when subjected to environmental stresses. Rice seedlings were subjected to 50, 100, 200, 400, 600, and 1000 mM H2O2 concentration for 3 d. This resulted to different reaction of leaf browning and 600 mM H2O2 concentration was selected to screen leaf and plant samples. For UV treatment, seedlings were exposed to artificial UV light at 30 cm height. Results showed that 3 out of 13 fully characterized lesion mimic mutant lines had 50% survival under ultraviolet stress and 10 out of 52 other lesion mimic mutants were found to be tolerant to H2O2 better than the wild type Dongjin. Our investigation indicated that H2O2 could be used as selectable marker in the early detection of resistant lines to related abiotic stresses where H2O2 has been involved. H2O2 is known as a regulatory molecule in stress perception and signal transduction.